Effect of Mechanical Abrasion on Oil/water Contact Angle in Metals - (:unkn) unknown (My University, 2012)
In this study the oil/water angle for brass, aluminum, hastelloy and 316 stainless steel was experimentally studied as a function of surface roughness. Samples were mechanically abraded by sandpaper in the way that all the scratches were parallel. Surface roughness was measured by profilometer, Nano-Indenter, and Atomic Force Microscope (AFM). The relationship between sandpaper particle size and surface roughness for all four metals was established. The highest surface roughness obtained for steel 316 ground by 180 grit sandpaper (1.23µm) and the smoothest surfaces were achieved for brass and aluminum after grinding with alumina (0.03 µm).Then oil/water contact angles were measured by Rame Hart Goniometer. Results showed that contact angle on brass increases with increasing the surface roughness from 88° on smooth brass to 128° on 60 grit ground sample. Smooth hastelloy had a contact angle (97°) lower than rough sample (110°). Contact angle of oil in water on fine polished aluminium decrease from 122° to 108° on 1200 grit and then increases with increasing the surface roughness to 125° on 60 grit. Contact angle of oil on steel increases from 83° on fine polished to 97° on 320 grit and then decreases with increasing the surface roughness and reach 77° on 60 grit. A model is presented for calculating Rf and fso when samples are ground parallel with sandpaper of known particle size and surface roughness and they have been used to calculate contact angle for both Wenzel and Cassie-Baxter types of contacts. Predicted values were compared with experimentally measured values. Results showed that aluminum followed Wenzel model, brass and hastelloy followed Cassie-Baxter model and stainless steel 316 exhibited a transition from Wenzel to Cassie-Baxter with a change in Rf.
Keywords: Contact Angle; Mechanical Abrasion; Modeling